2022
DOI: 10.21203/rs.3.rs-1926171/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of the evolutionary phylodynamic of Delta and Omicron variants of SARS-CoV-2

Abstract: Due to the inconsistency of the information regarding the evolution of the last two waves caused by the Delta and Omicron variants, we are attempting to provide a phylodynamic analysis. We used the nucleotide sequences of the Delta (n = 89) and Omicron (n = 74) variants recorded in the GISAID database to perform an analysis based on the contemporary model of the birth-death horizon. An average rate of evolution of 3.677 × 10− 4 subs /site/year (range,1.311× 10− 4−6.144×10− 4 ) for the DELTA variant, this gives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The role of vaccination in shaping the evolution of SARS-CoV-2 merits further research. Finally, our estimated evolutionary rate of AY.57 lineage was within the range of previously estimated values for the Delta variant [36,40].…”
Section: `15supporting
confidence: 84%
See 2 more Smart Citations
“…The role of vaccination in shaping the evolution of SARS-CoV-2 merits further research. Finally, our estimated evolutionary rate of AY.57 lineage was within the range of previously estimated values for the Delta variant [36,40].…”
Section: `15supporting
confidence: 84%
“…Our estimated dN/dS ratio for entire coding region suggested that the evolution of AY.57 lineage was driven by a weak purifying selection, although this varied across the virus genome, with ORF1b, ORF3a, E gene and ORF7a exhibiting a positive selection. Of note, a recent report showed that the vaccines had played a role in selective adaptation of SARS-CoV-2 Delta variant [39]. As a consequence, different mutation profiles were recorded between vaccine breakthrough infection and non-breakthrough infection groups [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3.898 x 10 -3 subs/site/year (range: 2.686 x 10 -3 to 5.102 x 10 -3 ) and 3.677 × 10 -4 subs/site/year (range: 1.311 x 10 -4 to 6.144 x 10 -4 ) for the Omicron and Delta variants, respectively. 61 Alterations in amino acids that decrease viral fitness are often eliminated by negative selection, while changes that improve viral fitness are retained by positive selection. On the other hand, amino-acid alterations are regarded as "neutral" when they have no effects on viral fitness.…”
Section: Discussionmentioning
confidence: 99%